Flavonoids and anthocyanins in seagrasses: implications for climate change adaptation and resilience - Botes, Jana; Ma, Xiao; Chang, Jiyang; Van de Peer, Yves; Berger, Dave Kenneth (Frontiers in Plant Science, 2025)
Seagrasses are a paraphyletic group of marine angiosperms and retain certain adaptations from the ancestors of all embryophytes in the transition to terrestrial environments. Among these adaptations is the production of flavonoids, versatile phenylpropanoid secondary metabolites that participate in a variety of stress responses. Certain features, such as catalytic promiscuity and metabolon interactions, allow flavonoid metabolism to expand to produce novel compounds and respond to a variety of stimuli. As marine environments expose seagrasses to a unique set of stresses, these plants display interesting flavonoid profiles, the functions of which are often not completely clear. Flavonoids will likely prove to be effective and versatile agents in combating the new host of stress conditions introduced to marine environments by anthropogenic climate change, which affects marine environments differently from terrestrial ones. These new stresses include increased sulfate levels, changes in salt concentration, changes in herbivore distributions, and ocean acidification, which all involve flavonoids as stress response mechanisms, though the role of flavonoids in combatting these climate change stresses is seldom discussed directly in the literature. Flavonoids can also be used to assess the health of seagrass meadows through an interplay between flavonoid and simple phenolic levels, which may prove to be useful in monitoring the response of seagrasses to climate change. Studies focusing on the genetics of flavonoid metabolism are limited for this group, but the large chalcone synthase gene families in some species may provide an interesting topic of research. Anthocyanins are typically studied separately from other flavonoids. The phenomenon of reddening in certain seagrass species typically focuses on the importance of anthocyanins as a UV-screening mechanism, while the role of anthocyanins in cold stress is discussed less often. Both of these stress response functions would be useful for adaptation to climate change-induced deviations in tidal patterns and emersion. However, ocean warming will likely lead to a decrease in anthocyanin content, which may impact the performance of intertidal seagrasses. This review highlights the importance of flavonoids in angiosperm stress response and adaptation, examines research on flavonoids in seagrasses, and hypothesizes on the importance of flavonoids in these organisms under climate change.